1981
DOI: 10.1007/bf00199489
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of antitumor immunity with ribonucleic acid-containing spleen extract of immunized animals

Abstract: Ribonucleic acid-containing spleen extract (i-extract) was prepared from the spleens of C57BL/6 mice immunized with mammary carcinoma Ca755. The i-extract contained a factor which could transfer antitumor immunity into the recipient mice, since the tumor growth was significantly retarded if mice received IP injections of i-extract at the same time as or at 6 days after tumor transplantation. Little or no inhibition of tumor growth was observ, ed in mice which received injections of i-extract 6 days prior to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
1982
1982

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…We reported previously that whole cells of an attenuated strain of Salmonella enteritidis enhanced the anti-tumor immunity of hosts that had been given transplants of mammary carcinoma [3]. We also reported that mini-cells of an avirulent strain of Salmonella typhimurium enhanced cellular but did not humoral immunity, and that the enhancing activity of mini-cells might be independent of the lipopolysaccharide of Salmonella cells [5].…”
Section: Introductionmentioning
confidence: 86%
“…We reported previously that whole cells of an attenuated strain of Salmonella enteritidis enhanced the anti-tumor immunity of hosts that had been given transplants of mammary carcinoma [3]. We also reported that mini-cells of an avirulent strain of Salmonella typhimurium enhanced cellular but did not humoral immunity, and that the enhancing activity of mini-cells might be independent of the lipopolysaccharide of Salmonella cells [5].…”
Section: Introductionmentioning
confidence: 86%